Satoshi Okada : Casa a Togoshi (2003)
Vivienda individual en las afueras de Tokio, año 2002.
Keywords: SATOSHI OKADA ARCHITECTS; VIVIENDAS UNIFAMILIARES; VIVIENDAS URBANAS; JAPON; TOKYO; OKADA, SATOSHI